Minority game: The battle of adaptation, intelligence, cooperation and power - Eguchi, A; Nguyen, H (2011)
Minority game is a simulation of a zero-sum game, which has a similar structure to that of a real world market like a currency exchange market. We discuss a way to implement the game and provide a simulation environment with agents that can use various types of strategies to make decisions including genetic algorithms, statistics, and cooperative strategies. The goal of this simulation study is to find the effective strategies for winning the zero-sum game. Results show that both honesty and dishonesty can lead to a player's success depending on the characteristics of the majority of players. © 2011 Polish Info Processing Soc.